2005
DOI: 10.1103/physrevb.71.134526
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality of superconductivity and vortex dynamics in the infinite-layer cuprateSr0.9M0.1CuO2

Abstract: The high magnetic-field phase diagram of the electron-doped infinite layer high-temperature superconducting ͑high-T c ͒ compound Sr 0.9 La 0.1 CuO 2 was probed by means of penetration depth and magnetization measurements in pulsed fields to 60 T. An anisotropy ratio of 8 was detected for the upper critical fields with H parallel ͑H c2 ab ͒ and perpendicular ͑H c2 c ͒ to the CuO 2 planes, with H c2 ab extrapolating to near the Pauli paramagnetic limit of 160 T. The longer superconducting coherence length than t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…[4,5,9,66]. Moreover, strong quantum fluctuations are expected due to proximity to quantum criticality [9,10,85,86] Macroscopically, the presence of COs and strong quantum fluctuations naturally lead to weakened superconducting stiffness upon increasing T and magnetic field H, [9,85,87,88] which may be responsible for the extreme type-II nature and the novel vortex dynamics of cuprate superconductors, [85,86,89,90,91,92,93,94,95] as schematically illustrated in Figs. 4(a) and 4(b) for the magnetic field (H) vs. temperature (T ) vortex phase diagrams of cuprate superconductors for H ĉ-axis and H ⊥ĉ-axis, respectively.…”
Section: Unconventional Low-energy Excitations In the Cupratesmentioning
confidence: 99%
See 3 more Smart Citations
“…[4,5,9,66]. Moreover, strong quantum fluctuations are expected due to proximity to quantum criticality [9,10,85,86] Macroscopically, the presence of COs and strong quantum fluctuations naturally lead to weakened superconducting stiffness upon increasing T and magnetic field H, [9,85,87,88] which may be responsible for the extreme type-II nature and the novel vortex dynamics of cuprate superconductors, [85,86,89,90,91,92,93,94,95] as schematically illustrated in Figs. 4(a) and 4(b) for the magnetic field (H) vs. temperature (T ) vortex phase diagrams of cuprate superconductors for H ĉ-axis and H ⊥ĉ-axis, respectively.…”
Section: Unconventional Low-energy Excitations In the Cupratesmentioning
confidence: 99%
“…The dashed curve represents the phase boundary modified by magnetic field misalignment and stacking faults that tend to smear the modulations of the S/IS to VL phase boundary and reduce the phase boundary into being monotonically dependent on H. (c) For H ab, assuming dominating quantum fluctuations associated with the proximity to quantum criticality and competing orders. [9,10,85,86] superconductivity. Above all, the one-gap model cannot provide natural explanations for all of the non-universal and unconventional low-energy excitations (e.g.…”
Section: "One-gap" Versus "Two-gap" Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…This PG has only been observed in hole-type cuprates and is found to correlate with the onset of the Nernst effect [1,11,12]. Our recent studies of the quasiparticle spectral density function and the DOS of various optimally doped cuprates [13] have revealed that the occurrence (absence) of the low-energy PG in hole-(electron-) type cuprate superconductors and the dichotomy in quasiparticle coherence [9,14] can be quantitatively understood as the result of a ground state consisting of coexisting competing orders (COs) and SC [15,16,[18][19][20][21][22] with the presence of finite quantum fluctuations [6,23,24]. The objective of this work is to expand on our previous work [13] to further investigate how the coexistence of COs and SC may influence the doping and momentum dependence of the low-energy quasiparticle excitations in different cuprates.…”
Section: Introductionmentioning
confidence: 99%